Partnership and Participation in a Northern Church-Southern Church Relationship - Scheffler, Marcia (Transformation, 2008)
The African church has been identified by many as a key factor in the struggle against HIV/AIDS. Not only are international funding organizations and Christian NGOs looking to partner with the local church, but some northern churches are also looking to bypass NGOs and enter into a direct relationship with the African church. This article fuses political and theological theories and analysis such as participatory development theory, democratic administration and transformational development in a case study of partnership between a Canadian church and a Zimbabwean church.